2019
DOI: 10.1161/circulationaha.118.035889
|View full text |Cite
|
Sign up to set email alerts
|

BOLA (BolA Family Member 3) Deficiency Controls Endothelial Metabolism and Glycine Homeostasis in Pulmonary Hypertension

Abstract: Background-Deficiencies of iron-sulfur (Fe-S) clusters, metal complexes that control redox state and mitochondrial metabolism, have been linked to pulmonary hypertension (PH), a deadly vascular disease with poorly defined molecular origins. The BolA Family Member 3 (BOLA3) regulates Fe-S biogenesis, and mutations in BOLA3 result in multiple mitochondrial dysfunction syndrome, a fatal disorder associated with PH. The mechanistic role of BOLA3 in PH remains undefined. Methods-In vitro assessment of BOLA3 regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 50 publications
4
72
1
Order By: Relevance
“…Many studies have started to dissect the immunological events that underlie SchPH pathogenesis (1,61,87,89,92,96,97,(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114). The current understanding of the signaling events is summarized in Figure 6.…”
Section: Current Concepts Of Schpah Disease Pathogenesismentioning
confidence: 99%
“…Many studies have started to dissect the immunological events that underlie SchPH pathogenesis (1,61,87,89,92,96,97,(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114). The current understanding of the signaling events is summarized in Figure 6.…”
Section: Current Concepts Of Schpah Disease Pathogenesismentioning
confidence: 99%
“…Intense immunoreactivity for ferritin-H ( Figure 5D) suggested that most Fe 3+ was likely bound in an unreactive form, leaving Hb and Fe 2+ as the primary prooxidant iron species with SCD PH lung macrophages. We further explored the localization of iron (as iron-sulfur, Fe-S) in mitochondrial ferredoxin proteins because Fe-S deficiencies have been implicated in PH (23,24). Ferredoxin reductase is shown colocalizing with mitochondria and iron, suggesting that intact Fe-S clusters in SCD PH ( Figure 5E).…”
Section: Characterization Of Iron Accumulation Within Scd Ph-associatmentioning
confidence: 99%
“…The potential molecular function of BolA proteins in functional cell types, particularly Bola3, remains to be resolved. Recently, Bola3 was reported to act a connective role between Fe-S-dependent oxidative respiration and glycine homeostasis in the process of endothelial metabolic re-programming, which is critical for pulmonary hypertension pathogenesis ( 21 ). Beige adipocyte is a re-programmed type of white adipocyte upon certain stimuli, and it largely depends on mitochondrial oxidative phosphorylation to drive thermogenesis ( 22 ).…”
Section: Introductionmentioning
confidence: 99%